Behavioural treatment for loud noise phobia in the minimal resources: a success parental involvement - Mat Zin, Nora; Razali , Ailin; Srinovianti , Noerdin (2009)
Loud noise phobia or ligyrophobia is one of the specific phobias occur in children. Like any other phobias, behaviour therapy is one of the effective treatment. The objectives are to illustrate a case of anxious ten years old girl who developed loud noise phobia which was triggered by explosion from firework since she was eight years old. It was severe enough to make anxious and fearful to any sudden loud noise. The effectiveness and limitation of behaviour therapy and the importance of parental motivation in treatment of childhood phobic disorder will be highlighted in this paper. Behaviour therapy using systemic desensitization technique was commenced. Limited resources did not stop the treatment process as her parent was educated to act like a 'co-therapist'.